Bentuk Tokoh Umar Maya Pada Wayang Sasak - Sunardy Kasim (Universitas Bumigora, 2019)
Puppet umar maya is known as one of the characters in the sasak puppet story. This figure acts as an advisor to the knights in the right puppets, especially the advisor to the king of the Jayangrana king. As an advisor, this figure has a wise, humble, smart, brave, and loyal character to his country. From these various characteristics, this figure is respected by all right-wing puppets and respected by his enemies. In this research, the writer tries to describe the shape of the virtual puppet umar figures with the hope that the community, especially the younger generation among academics, can know the form of the puppet sasak, especially the virtual umar figures. The research method that I use is a qualitative method where the data collection is done by observation, interviews with the actors of Sasak puppet art, as well as reviewing documents that discuss Sasak puppets. From the results of research conducted by the author, the results obtained in the form of a description of the shape of the virtual umar characters in sasak puppets which are divided into urayan about the shape of the virtual umar figures in terms of the form of making ideas of virtual umar characters and the physical form of the virtual umar characters in the sasak puppet